Beyond colonial miseducation internationalism and Deweyan pedagogy in the American-era Philippines - Claudio, Lisandro E. (Philippine Studies: Historical and Ethnographic Viewpoints, 2015)
This article maps early-twentieth-century Philippine pedagogy and nationalism through an intellectual biography of educator Camilo Osias (1889-1976). It examines Osias's thinking as informed by three theoretical movements: gradualist Philippine nationalism ("Filipinism"), nationalist internationalism, and the pragmatist philosophy of John Dewey. The synthesis of these three movements allowed Osias to sketch a pluralist, democratic, and deliberative philosophy of public engagement, which was mainstreamed through classrooms and educational institutions. Such ideas, although foreign to contemporary anti-imperial intellectuals, may serve as alternatives to inward-looking forms of nationalism.